PODMIOTY ZWIĄZANE Z PRZEPROWADZANIEM KONKURSÓW NA STANOWISKA KIEROWNICZE – PROBLEMATYKA PRAWNA - Duraj, Tomasz (Zeszyty Prawnicze, 2016)
ENTITIES INVOLVED IN THE ORGANISATION OF COMPETITIONS FOR MANAGERIAL POSTS: LEGAL ISSUES Summary The article discusses the legal issues associated with the competition method of selecting management staff. Under the current legal provisions in Poland many legal acts pertain to this issue, giving an inhomogeneous set of regulations for the principles of conducting such procedures in particular domains of public, social and economic affairs. The subject of the first part of this paper is the analysis of the concept of competitions for managerial posts and the classification of the procedure for the competitive selection of management staff based on various criteria. The author also points out the main advantages and disadvantages of competitions held for managerial posts. The second part of the paper describes the entities directly involved in the organisation of competitions for management staff, and indispensable for the running of such competitions. In my opinion the analysis of the legal acts which regulate this issue allows for the distinction of two essential categories of entities directly involved in the process of competitive management appointments. On the one hand this means those organisers who are responsible for initiating the whole procedure and who make the final decision on the appointment. On the other hand there is the competition commission, which has a significant influence on the effectiveness of the competitive selection of management staff.